Positive and negative emissions from cooling towers, part 1: Droplet measurements. Issue 1 (8th December 2022) - Leandro, Mason D.; Wallis, Christopher D.; Wexler, Anthony S.; Chuang, Patrick Y.
Abstract: Wet cooling towers are used in industrial processes, power plants, and heating, ventilation, and air conditioning systems. Their purpose is to reject waste heat from a system through evaporative cooling of process water. Due to their design, a small fraction of process water is emitted from the tower exit, termed "spray drift." Dissolved solids contained within spray drift droplets are regulated as PM10 emissions by EPA AP-42. Here, we use a novel instrumentation package to measure particulate emissions from drift droplets at two cooling towers located at separate power plants. We find that drift droplet properties depend on the sampling position over the tower so multiple positions need to be sampled to accurately estimate emissions. We estimate 11 and 3.3 grams of PM10 are emitted from each tower per hour, with 78% and 87% of PM10 emissions also qualifying as PM2.5 . AP-42 overestimates PM10 emissions by a factor of 2.4 for one tower and nearly 300 for the other. These results suggest that AP-42 may require revision to both accurately reflect lower PM10 emissions and account for unregulated PM2.5, which constitute the majority of emissions. Copyright © 2022 American Association for Aerosol Research Graphic Abstract: UF0001